AIR-SAND BLOWING PROCESS – A RETROSPECTIVE AND CURRENT STATE - G. I. Pasyuk; A. P. Melnikov; A. V. Pashkevich; A. V. Cherapovich; V. V. Fonov (Литьë и металлургия)
Information on researches and design development in the field of air-sand blowing process and creation of core-blowing installations which were carried out in 1950–1960 is provided in the article. The reference is made to the scientific centers and concrete design engineers who performed the specified activities.The essence of air-sand blowing process and the principles of its realization in core-making machines by design development and manufacture executed by the experts of NIILITAVTOPROMA (JSC BELNIILIT) is briefly stated.The main ratios of the areas between elements of system the sand-blowing installation systems, the basic rules and recommendations for design and manufacture of core-making machines and equipment for them are made. The retrospective of development and improvement of design solutions of air-sand blowing process is laid out. The essence and the modern design solution of caseless option of air-sand blowing process is stated. Illustrations of standard core-making machines for production of cores in the heated equipment and with amines blow are given. Systems the air-blowing devices, hold-down unit for blast and discharge and a special design of caseless option of sand-blowing process are described.The principle of rational combination of air-blowing process and process of a purging in modern blowing technologies is designated. The current trend of transition to computer design of system the air-blowing devices and its elements is shown (reference sections for boost, ventilation, etc.).